Small intestinal inflammation following oral infection with Toxoplasma gondii does not occur exclusively in C57BL/6 mice: review of 70 reports from the literature - Maximilian Schreiner; Oliver Liesenfeld (Memorias do Instituto Oswaldo Cruz, 2009)
Small intestinal immunopathology following oral infection with tissue cysts of Toxoplasma gondii has been described in C57BL/6 mice. Seven days after infection, mice develop severe small intestinal necrosis and succumb to infection. The immunopathology is mediated by local overproduction of Th1-type cytokines, a so-called "cytokine storm". The immunopathogenesis of this pathology resembles that of inflammatory bowel disease in humans, i.e., Crohn's disease. In this review, we show that the development of intestinal pathology following oral ingestion of T. gondii is not limited to C57BL/6 mice, but frequently occurs in nature. Using a Pubmed search, we identified 70 publications that report the development of gastrointestinal inflammation following infection with T. gondii in 63 animal species. Of these publications, 53 reports are on accidental ingestion of T. gondii in 49 different animal species and 17 reports are on experimental infections in 19 different animal species. Thus, oral infection with T. gondii appears to cause immunopathology in a large number of animal species in addition to mice. This manuscript reviews the common features of small intestinal immunopathology in the animal kingdom and speculates on consequences of this immunopathology for humankind.